(untitled) (Journal of Comparative Social Work, 2013)
The turmoil created by the financial crisis and economic recession in Europe has served as an impetus for austerity measures in many countries. In this article, we ask whether these crises have also triggered reforms in family policy, and we focus on three European welfare states – Finland, Germany and the United Kingdom – countries that are often considered members of different family policy regimes. The article addresses two main research questions. The first one relates to the number, direction and magnitude of family policy reforms in these three countries since the beginning of the financial crisis in 2008/2009, while in the second we discuss whether the reforms observed during this period can be seen as being related to the financial crisis and its later repercussions on the Euro-zone area, or if there are other explanations.